Organizational Health Index In A State-Owned Enterprise: A Case Study At PT. Waskita Karya Headquarters - Hibatullah, Bariq Rizki; Pratama, Andika Putra (Journal of Business and Management, 2019)
An organization’s health is an ability to align around and achieve strategic goals and is critical for long-term performance. However, according to McKinsey (2010), many leaders overlook organizational health because they lack a clear way to measure and improve it. Organizational Health Index (OHI) applies analytical rigor to organizational health management. The Organizational Health Index solution measures and tracks the organizational elements that drive performance. It provides a simple but powerful road map for leaders and managers to improve organizational health (Mckinsey, 2010). As a State-Owned Enterprise, Waskita has never conducted organizational health assessment. The author gained this information by conducting a pre-research interview with the secretary of Human Capital Management division in Waskita. The health of the organization within the company is very influential in the work performance of the company itself. If we associate with the Waskita case and the development of the Indonesia infrastructure that is being launched, then OHI will be very useful for Waskita. Moreover, Waskita is one of leading state companies in Indonesia which plays a major role in the development of the country. Then, OHI is important in order for Waskita to monitor and maintain performance to expedite the country’s infrastructure development process. The researcher will use the type of research in the form of quantitative, because quantitative business research can be defined as business research that addresses the purpose of research through empirical assessments involving measurement and numerical analysis approaches. When looking at the mean score of each practice without being grouped into archaetype, the practice of open and trusting contributes greatly to the formation of Organizational Health Index in Waskita. This is followed by employees’ priorities for the capability and impact of motivation on the work environment. On the contrary, we can see that the leadership aspect in Waskita contributes little to the formation of Organizational Health Index in Waskita. From the point of view archaetype grouping Organizarional Health Index in Waskita can be developed on the knowledge core aspect. This is because Waskita has not prioritized knowledge core practice to the fullest. If we look at each practice without groping archaetype, the leadership aspect can be developed to contribute more to the formation of Organizational Health Index in Waskita. Furthermore, the author recommends that Waskita should focus on pursuing leadership driven and market focus archaetypes in order to fulfil its vision and mission.Key words: Organizational Health Index, State-Owned Enterprise